2019
DOI: 10.1017/s0010417519000045
|View full text |Cite
|
Sign up to set email alerts
|

On Principals and Agency: Reassembling Trust in Indian Ocean Commerce

Abstract: The role of trust in long-distance trade has been a topic of inquiry and debate among economists, sociologists, and historians. Much of this literature hinges on the social, legal, and economic structures that undergird, if not obviate, the concept of trust. This article draws on assemblage theory to suggest that trust in Indian Ocean trade is better understood as a key component of a commercial assemblage. Laws or social mores are not external to but rather enrolled within an assemblage constituted by people,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Among Indian export traders in Yiwu, then, mistrust is valued and cultivated as an indispensable practical resource which allows the negotiation of the vagaries and volatilities of international trade under conditions of intense competition and what are experienced as restrictive regulations. Reflecting on the contentious business partnership between an Indian merchant and his Somali agent in early twentieth-century Aden, historian Johan Mathew (2019: 245) cogently writes that, ‘Trust is often experienced as a “gut feeling”. It does not itself mitigate risk, but it does make that risk palatable.’ In the case of Indian export agents in Yiwu, however, what is elicited might not be simply a ‘gut feeling’ about the trustworthiness of others, but, as Gafoor told us at the beginning of this article, the trust in one's own luck and capacity to navigate successfully the vagaries and risks of trade.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Among Indian export traders in Yiwu, then, mistrust is valued and cultivated as an indispensable practical resource which allows the negotiation of the vagaries and volatilities of international trade under conditions of intense competition and what are experienced as restrictive regulations. Reflecting on the contentious business partnership between an Indian merchant and his Somali agent in early twentieth-century Aden, historian Johan Mathew (2019: 245) cogently writes that, ‘Trust is often experienced as a “gut feeling”. It does not itself mitigate risk, but it does make that risk palatable.’ In the case of Indian export agents in Yiwu, however, what is elicited might not be simply a ‘gut feeling’ about the trustworthiness of others, but, as Gafoor told us at the beginning of this article, the trust in one's own luck and capacity to navigate successfully the vagaries and risks of trade.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, in Yiwu's export trade there are no hard-and-fast means to determine in advance whether or not any particular market player would prioritize relationships based on mutuality and trust over short-term gains. 11 If export agents share many of the broad characteristics and business orientations of colonial or post-colonial 'commission agents', they also experience similar conditions of precarity and instability (Mathew 2019). Against the predictions that informal mediation would wither away once both capital and democracy reached 'maturity', recent research has shown that in postliberalization India, different modalities of brokerage have flourished (see, for example, Picherit 2009; Roesch 2009; Björkman 2021; cf.…”
Section: Indian Export Agents In Yiwumentioning
confidence: 99%
See 2 more Smart Citations
“…Here, expectations of betrayal rather than trust appear common in traders' networks of co-ethnics. While there is no doubt that trust, systemic or interpersonal (Mathew 2019;Tilly 2005), is useful for long-term and long-distance trade, attitudes, strategies and types of alliances among traders in Georgia show us that trusting relationships are not people's main concern. On the contrary, it is people's ability to maintain relationships in the absence of trust, often in violation (or temporary suspension) of some cultural norms, deeply felt political emotions, historical memory and so on, that is often at stake.…”
Section: National Borders Historical Animosities: Political Emotionsmentioning
confidence: 99%